(untitled) (Contemporary Journal of Social Science Review, 2025)
The research was designed to investigate the role of undergraduate physical education (PE) taught curriculum in developing inclusive teaching self-efficacy amongst undergraduate sports sciences and physical education students in Punjab Pakistan. The researcher used stratified random sampling to recruit 2,000 undergraduate sports sciences and physical education students from different universities to participate in this research. The participants completed the Self-Efficacy in Inclusive Physical Education (SEIPE) scale, a fifteen (15) item instrument measuring undergraduate students’ confidence in teaching students with diverse learning needs. The results revealed that most of the participants expressed moderate level of self-efficacy , with 52.1% rating themselves “Fairly” and 43.6% “To some extent.” Very few (0.8%) indicated absolute confidence in inclusive teaching. An independent samples t-test revealed no significant gender differences in mean SEIPE scores (male M = 2.39, SD = .37; female M = 2.40, SD = .36; t(1998) = –.89, p = .37). The findings of present research suggest that the current undergraduate PE curriculum builds baseline awareness amongst students but does not adequately develops high level inclusive teaching confidence in them. The study emphasizes the need for curriculum reforms embedding Universal Design for Learning (UDL), adaptive practicum experiences, and differentiated instruction strategies.